PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PASIEN PADA RUMAH SAKIT HERMINA PALEMBANG - Aryuningtyas Jiwa Pradhini; Marlina Widiyanti; Muchsin Saggaff Shihab; Aslamia Rosa (Jurnal Ilmiah Global Education, 2023)
This research was conducted aiming to determine the effect of service quality and corporate image on patient decisions at Hermina Palembang Hospital. The population in this study were all patients seeking treatment at the Executive Polyclinic at Hermina Palembang Hospital. The sampling technique used in this study was purposive sampling, so the sample in this study was 100 respondents. The results of multiple linear analysis show that service quality and corporate image have a positive and significant effect on patient decisions at Hermina Palembang Hospital. It is hoped that the management of Hermina Palembang Hospital can evaluate the quality of service in the Pharmacy section, where queues often occur considering that not all prescribed drugs can be given directly to patients. This requires an improvement of the system, either by adding more adequate facilities/infrastructure or by adding additional human resources if necessary so that queues at the Pharmacy section do not occur again. Corporate image, it is hoped that the management of Hermina Palembang Hospital will upgrade more competent tools, facilities or medical personnel. Considering that there are more and more types of private hospitals in Palembang, the competition will be even more rapid. By adding good facilities, tools and human resources, it will provide its own charm to attract prospective patients to seek treatment at Hermina Palembang Hospital.